Improving The Quality of Islamic Cultural History Learning : Teacher Strategy at Madrasah Aliyah (Program Studi Magister Pendidikan Agama Islam Universitas Hasyim Asy’ari Tebuireng Jombang m Asy'ari, 2023)
This research aims to find out the strategies of PAI teachers in teaching SKI subjects at MASS Tebuireng to improve the quality of their learning. This study used a qualitative approach using three data collection methods: observation, interviews, and documentation. To analyze the data, it was carried out through three channels, namely data reduction, data presentation, and drawing conclusions. This study obtained the results that the SKI learning at MASS Tebuireng was in accordance with the 2013 curriculum implemented in the ministry of religion. Islamic cultural history subject in the Madrasah Aliyah curriculum is one of the subjects of Islamic Religious Education which is directed at preparing students to know, understand, and live the history of Islamic culture which will later become the basis of his outlook on life through guidance, training, teaching, use of experience and habituation. The PAI teacher's strategy in teaching SKI subjects at Madrasah Aliyah Salafiyah Safi`iyah Tebuireng Jombang has been carried out by following the proper procedure steps, namely by giving directions to motivate students first, then dividing them into several groups, then showing a video about the material being taught, then they were given the task of pursuing material to make stories, then representatives from each group presented the results, conducted questions and answers and finally the teacher evaluated them.